Risk Factors of Stunting and Wasting in Toddler During the Covid-19 Pandemic - Maghfirah Maghfirah; Aripin Ahmad; Meutia Zahara; Irwan Saputra; Asnawi Abdullah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a child's height growth that is shorter than their age. Wasting is the development of a child's weight that is too thin to their height. In 2019, the prevalence of Stunting cases that occurred in the world was 21.3%, and the prevalence of Wasting cases was 6.9%. The pandemic situation has disrupted nutritional services, especially in health service facilities and integrated health posts, due to the lack of community mobility. This study aims to determine the risk factors for stunting and wasting in toddlers during the Covid-19 pandemic. This study is descriptive analytical with a cross-sectional design. The population in this study were toddlers under two years of age. The sample in this study was 93 using a purposive sampling technique. The data collection method was carried out using a validated questionnaire and interviews using the Chi-Square statistical test. The results of the analysis showed that the most dominant risk factor for Stunting was Exclusive Breastfeeding (OR = 9.37; 95% CI: 2.14-40.86; p = 0.003); The most dominant risk factor for Wasting is Environmental Sanitation (OR=16.44; 95%CI: 3.68-73.47; p=0.000) and the most dominant risk factor for Stunting plus Wasting is Environmental Sanitation (OR=3.86; 95%CI: 1.39-10.75; p=0.009). For Nutrition Program Managers, it is important to improve the nutritional status and nutrient intake levels of the community, especially after the pandemic ends.